Effect of adjunctive glucose-lowering drugs on body weight in people with type 1 diabetes: a systematic review and network meta-analysis protocol. Issue 11 (14th November 2020) - Laugesen, Christian; Ranjan, Ajenthen G.; Schmidt, Signe; Rasmussen, Lauge Neimann; Nørgaard, Ole; Christensen, Robin; Nørgaard, Kirsten
Abstract : Introduction: Obesity increases the risk of comorbidities and diabetes-related complications and, consequently, efforts to prevent and reduce excess weight in people with type 1 diabetes are essential. The aim of this systematic review and network meta-analysis is to assess the effect of adjunctive glucose-lowering drugs on body weight and other important health outcomes in people with type 1 diabetes. Methods and analysis: This systematic review and network meta-analysis will include randomised controlled trials (RCTs) evaluating the use of adjunctive glucose-lowering drugs for treatment of people with type 1 diabetes. MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, ClinicalTrials.gov and WHO International Clinical Trials Registry Platform will be searched from inception to present. Key eligibility criteria include: RCT study design; adult participants with type 1 diabetes; treatment with a glucose-lowering drug for ≥24 weeks; and comparison of the intervention to placebo, usual care or another glucose-lowering drug. The primary outcome is change in body weight. Other major outcomes include change in HbA1c and total daily insulin dose and risk of hypoglycaemia and other adverse events. Dual study selection, data extraction and risk of bias assessment will be performed. Results from the meta-analysis will be presented as weighted mean differences for continuous outcomes and risk ratios for dichotomous outcomes. Sources of heterogeneity will be explored by subgroup and sensitivity analysis. A network meta-analysis for the primary outcome will be performed using an arm-based random-effects model based on the Bayesian framework while assessing for transitivity across studies and consistency between direct and indirect estimates. The overall quality of the evidence will be assessed using the Grading of Recommendations, Assessment, Development and Evaluation approach for each outcome. Ethics and dissemination: No ethical assessment is required. The results of this review will be disseminated through peer-reviewed publication and conference presentation. PROSPERO registration number: CRD42020158676